Derivation of iPSC line (RCMGi002-A) from dermal fibroblasts of a cystic fibrosis female patient with homozygous F508del mutation - Ekaterina Kondrateva (Stem Cell Research, 2021)
Cystic fibrosis is one of the most common inherited diseases caused by mutations in CFTR gene, of which F508del is the most frequent. Currently, the possibility of cell therapy including genome editing is widely discussed. We generated induced pluripotent stem cells from fibroblasts obtained from a 22-year-old woman with clinically manifested and genetically proven disease by using non-viral, non-integrating RNA reprogramming vector that contains five reprogramming factors: OCT4, KLF4, SOX2, GLIS1, and c-MYC. The established cell line can express endogenous pluripotency markers, possesses a normal karyotype, and has the ability to differentiate into three germ layers in spontaneous differentiation assay.